2012
DOI: 10.1590/s2176-94512012000600023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cephalometric pattern of Brazilian achondroplastic adult subjects

Abstract: OBJECTIVE: The aim of this study was to assess the position of the cranial base, maxilla, and mandible of Brazilian achondroplastic adult subjects through cephalometric measurements of the cranio-dento-facial complex, and to compare the results to normal patterns established in literature. METHODS: Fourteen achondroplastic adult subjects were evaluated based on their radiographic cephalometric measurements, which were obtained using the tracings proposed by Downs, Steinner, Bjork, Ricketts and McNamara. Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…The presence of mandible abnormalities in these diseases has rarely been studied. A report showed mandibular clefting in a case of TD I (28), two cephalometric studies in adult ACH patients reported opposite results concerning the size of the mandible [normal for Cohen et al (26) or decreased for Cardoso et al (27)], whereas another study showed that MS patients had shorter mandibular body length than controls (29). Several mouse lines carrying Fgfr3 activating mutations have been generated but a very few comprehensive analysis of the mandible are available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of mandible abnormalities in these diseases has rarely been studied. A report showed mandibular clefting in a case of TD I (28), two cephalometric studies in adult ACH patients reported opposite results concerning the size of the mandible [normal for Cohen et al (26) or decreased for Cardoso et al (27)], whereas another study showed that MS patients had shorter mandibular body length than controls (29). Several mouse lines carrying Fgfr3 activating mutations have been generated but a very few comprehensive analysis of the mandible are available.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of lateral cephalogram from adult ACH patients has shown a prognathic mandible (i.e. anteriorly displaced) (26,27). It has also been reported that in humans, other skeletal dysplasia caused by activating mutations of FGFR3 can result in mandibular dysmorphogenesis as seen in thanatophoric dysplasia (TD) (28), and Muenke syndrome (MS) (29).…”
Section: Introductionmentioning
confidence: 99%
“…Because of hypoplasia of midfacial structures [305] malocclusion is common. In addition to maxillary hypoplasia, there is relative overgrowth of the mandible; it is uncertain whether mandibular growth is itself normal [305] or diminished [306] but less so than is the diminishment of maxillary growth. Given these features, one might expect an extensive literature concerning management of malocclusions in those with achondroplasia; it is surprising how little literature concerning this is available [307312].…”
Section: Natural History and Managementmentioning
confidence: 99%
“…Interdependencies between cranial structures and odontometric parameters using cephalometric analysis by Downs, Steinner, Bjork, Ricketts and McNamara were found when working with the Brazilian population sample [7,18].…”
Section: Discussionmentioning
confidence: 95%